PEMANFAATAN POJOK LITERASI SEBAGAI SOLUSI DAMPAK PEMBELAJARAN DARING ERA COVID-19 UNTUK ANAK USIA 5-12 TAHUN DI DESA ROGOJAMPI - Yeni Rokhilawati (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
With the Covid-19 pandemic, it requires the world of education to eliminate activities in schools. Therefore replace it with an online method. Because students aged 5-12 are still unable to adapt, then. KKN 2021 students have a program that accompanies children aged 5-12 years so that they do not miss lessons through the literacy corner. There students guide children aged 5-12 years to be able to follow online learning. Based on the main problem, the approach used in community service in rogojampi village using method, participatory action research (PAR), is one of the methods used to explore the problems and potential that exist in a community. From the results of the literacy corner program, people who have children aged 5-12 years no longer miss lessons and their parents are also no longer complicated to guide their children to be able to understand the material provided by teachers.